The Bible a very short introduction - Riches, John Kenneth 1939- (Oxford University Press, 2000)
This study explores the importance of the Bible in different communities and cultures and attempts to explain why it has such a variety of uses and interpretations
Includes bibliographical references and index
Keywords: Bible / Introductions